2016
DOI: 10.1007/s13312-016-0900-6
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus infection in children with acute gastroenteritis in Aurangabad, Central Maharashtra

Abstract: Rotavirus diarrhea was caused mainly by G1P[8] strains during 2012-2013 in Aurangabad, Central Maharashtra, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…On G and P combined typing G3P[8] was the most common genotype (133; 51.9%), followed by G1P[8] (44; 17.18%); this is different from other studies from various parts of the country where G1P[8] was the most prevalent strain. 9 22 23 24 Though G1P[8] was the most common genotype in the majority of the country, G3P[8] is the emerging strains in this region, which is similar to prior studies from this part of the country that showed G3P[8] as the most prevalent strain. 15 16 Another study from this belt suggested G1P[8] to be the most prevalent strain.…”
Section: Discussionsupporting
confidence: 80%
“…On G and P combined typing G3P[8] was the most common genotype (133; 51.9%), followed by G1P[8] (44; 17.18%); this is different from other studies from various parts of the country where G1P[8] was the most prevalent strain. 9 22 23 24 Though G1P[8] was the most common genotype in the majority of the country, G3P[8] is the emerging strains in this region, which is similar to prior studies from this part of the country that showed G3P[8] as the most prevalent strain. 15 16 Another study from this belt suggested G1P[8] to be the most prevalent strain.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, overall 39.87% and 39.24% samples were found to be positive for rotavirus by PAGE and RT-PCR, respectively. An earlier study from Western India reported 47% of samples from unvaccinated children collected from Pune and 11.9% samples from Aurangabad to be positive for rotavirus ( Jain et al., 2016 ; Maher et al., 2016 ). Higher positivity was observed in Goa than Meghalaya.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the proportion of G3 strains (P[8] and P[6]) was significantly higher with the P[8] as the dominant genotype (80.3%) followed by P[6] (14.6%) among patients admitted to the hospital with severe dehydrating diarrhea ( Athiyyah et al., 2019 ) was observed in Indonesia. Limited studies on rotaviral genotypes in Eastern India revealed G1 (57%) as the most predominant type followed by mixed types (20%), G2 (13%) and G4 (9%) (NICED, Annual Report, 2002–03), while, G1P[8] genotype was frequently isolated from Western India ( Chitamber et al., 2012 ; Jain et al., 2016 ; Maher et al., 2016 ). However, shift in dominating strains from the G1P[8] to G3P[8] was observed in 2016 from Eastern part of India ( Banerjee et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%